BASIC SUPPLY CHAIN BAWANG MERAH (ALLIUM ASCALONICUM L) DI KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA DARI PERSPEKTIF SISTEM DINAMIS - Widodo, Kuncoro Harto; Rembulan, Dewi (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
Shallot (Allium ascalonicum L) is a valuable agro-industrial commodity for community. The demand of the commodity in Indonesia increase progressively in the few years so that shallot is one of the pre-eminent products of Bantul Regency. Delays in shallot supply from local farmers stems from various problem in supply chain which is very dynamic. This study analyzes these problems from supply chain point of view by identifying the behavior of the system and by analyzing the relationships between the components. The study, then, describe their behavior within the supply chain by using a dynamic system. We obtain that there is three basic groups : farmers, warehouse, and user. Each group plays a role in providing quality, quantity and avalaibility, post harvest technique, production cost, and selling price.These three big groups influences the others in terms of quality, quantity and shallot supply, post-harvest process, and cost and sale price.